Chagas Disease in the Non-Endemic Area of Rome, Italy: Ten Years of Experience and a Brief Overview - Maria Letizia Giancola; Andrea Angheben; Laura Scorzolini; Stefania Carrara; Ada Petrone; Antonella Vulcano; Raffaella Lionetti; Angela Corpolongo; Rosalia Marrone; Francesca Faraglia; Tommaso Ascoli Bartoli; Patrizia De Marco; et al. (MDPI AG, 2024)
Chagas disease (CD) is a parasitic infection endemic in Latin America and also affects patients in Western countries due to migration flows. This has a significant impact on health services worldwide due to its high morbidity and mortality burden. This paper aims to share our experience at the National Institute for Infectious Diseases "Lazzaro Spallanzani", IRCCS, in Rome, Italy, where to date, a total of 47 patients-mainly Bolivian women-diagnosed with CD have received treatment with benznidazole, with all but one presenting with chronic disease. Most of the patients were recruited through the first extensive screening program held in 2014 at our Institute. About a quarter of our patients showed adverse effects to benznidazole, including a case of severe drug-induced liver injury, but 83% completed a full course of treatment. In addition to the description of our cohort, the paper reports a brief overview of the disease compiled through a review of the existing literature on CD in non-endemic countries. The growing prevalence of CD in Western countries highlights the importance of screening at-risk populations and urges public concern and medical awareness about this neglected tropical disease. There are still many unanswered questions that need to be addressed to develop a personalized approach in treating patients.